Resource Risk and the Origins of Inequality: Evidence from a Pastoralist Economy - Konstantinos Angelopoulos; Spyridon Lazarakis; Rebecca Mancy; Dorice Agol; Elissaios Papyrakis (Center for Economic Studies and ifo Institute (CESifo), 2023)
Resource risk is a core ingredient of models of wealth inequality in modern economies, but remains understudied in explanations of inequality in early human and small-scale societies that can inform us about the origins of inequality. Resource risk generates variation in resources and leads to wealth inequality via savings decisions, given the available production and storage technology and the institutional arrangements that govern property rights and insurance. We examine whether this mechanism can explain wealth inequality in a pastoralist economy where wealth is held in livestock, production and storage technology resembles that of early human societies and there is virtually no financial market penetration. Our analysis uses original survey data from traditional Turkana pastoralist communities in Kenya to measure wealth inequality and relevant shocks to resources and to inform a model of wealth accumulation under resource risk. The data reveal substantial wealth inequality and resource risk, including via shocks to the growth rate of livestock holdings, which depends on droughts. Asset accumulation decisions also show that livestock is not used as a buffer stock with respect to shocks to livestock. The wealth accumulation model accurately reproduces the empirical wealth distribution while also predicting the pattern of asset accumulation decisions in response to different shocks to resources observed in the data. These results demonstrate that resource risk and the economic decision making it implies explain the wealth inequality observed in the Turkana pastoralist economy we study. Our findings highlight the role of the resource risk mechanism as a driver of inequality in a small-scale economy, suggesting its importance in the origins of inequality in early human societies.
Keywords: E21; N30; O15; D31; 330; origins of inequality; risk exposure; small-scale economy; Turkana pastoralists